A short-term high-fat diet alters rat testicular activity and blood-testis barrier integrity through the SIRT1/NRF2/MAPKs signaling pathways - Falvo, Sara; Minucci, Sergio; Santillo, Alessandra; Senese, Rosalba; Chieffi Baccari, Gabriella; Venditti, Massimo (Frontiers in Endocrinology, 2023)
Overweight/obesity are metabolic disorders resulting from behavioral, environmental, and heritable causes. WHO estimates that 50% of adults and 30% of children and adolescents are overweight or obese, and, in parallel, an ongoing decline in sperm quality and male fertility has been described. Numerous studies demonstrated the intimate association between overweight/obesity and reproductive dysfunction due to a highly intricate network of causes not yet completely understood. This study expands the knowledge on the impact of a short-term high-fat diet (st-HFD) on rat testicular activity, specifically on steroidogenesis and spermatogenesis, as well as focusing on the involved molecular mechanisms related to mitochondrial dynamics, blood-testis barrier (BTB) integrity, and SIRT1/NRF2/MAPKs pathways. Five weeks of HFD results in reduced steroidogenesis, increased apoptosis of spermatogenic cells, and altered spermatogenesis, as highlighted by reduced protein level of meiotic and post-meiotic markers. Further, we evidenced the compromission of the BTB integrity, as revealed by the downregulation of structural proteins (N-Cadherin, ZO-1, occludin, connexin 43, and VANGL2) other than the phosphorylation of regulative kinases (Src and FAK). At the molecular level, the impairment of mitochondrial dynamics (fission,